2019
DOI: 10.3390/ijerph16193694
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Implementing an Environmental Flow Regime in the Luvuvhu River Catchment, South Africa

Abstract: Rivers are now facing increasing pressure and demand to provide water directly for drinking, farming and supporting industries as a result of rapidly growing global human population. Globally, the most common practice for catchment managers is to limit water abstraction and changes to stream flow by setting environmental flow standards that guard and maintain the natural ecosystem characteristics. Since the development of the environmental flow concept and methods in South Africa, very few studies have assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Rivers of this catchment have shown a substantial decrease (>53%) in stream flow volume over the last 80 years (Odiyo, Makungo, & Nkuna, 2015). Kleynhans (1996) classified streams in the Luvuvhu River as fairly natural, but recent agricultural intensification and the expansion of human settlements have had substantial impacts on instream biota (Foord & Fouché, 2016), and the flow regime has consequently been altered considerably (Ramulifho, Ndou, Thifhulufhelwi, & Dalu, 2019).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Rivers of this catchment have shown a substantial decrease (>53%) in stream flow volume over the last 80 years (Odiyo, Makungo, & Nkuna, 2015). Kleynhans (1996) classified streams in the Luvuvhu River as fairly natural, but recent agricultural intensification and the expansion of human settlements have had substantial impacts on instream biota (Foord & Fouché, 2016), and the flow regime has consequently been altered considerably (Ramulifho, Ndou, Thifhulufhelwi, & Dalu, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…This is not surprising given the influence of stream regulation on stream flow which causes numerous changes (Bunn & Arthington, 2002), affecting hydraulic patterns (velocity and depth) and variation on mayfly assemblage structures (Brooks et al, 2005;Klonowska-Olejnik & Skalski, 2014;Salmaso et al, 2018). With increasing stream flow variability and declining stream flow volumes in the Luvuvhu catchment due to increasing water abstraction and climate variability (Kleynhans, 1996;MacFadyen, Zambatis, Astrid, Van, & Cang, 2018;Ramulifho et al, 2019), this may decrease abundance or diversity of mayfly as well their ecosystem services (Boyero et al, 2011).…”
Section: Drivers Of Assemblage Structuresmentioning
confidence: 99%
“…Flow regimes are heavily regulated in the systems studied, and it is probably the most important variable to consider when looking at fish responses (Saraiva Okello et al 2015;Riddell et al 2019;O'Brien et al 2018;Flitcroft et al 2016). Importantly, there is a need to mitigate the anthropogenic stressors that exasperate the natural stressors on fish behaviour (Rivers-Moore et al 2013;Saraiva Okello et al 2015;Ramulifho et al 2019). Flow changes presented in the study showed relatively low base flows during the low flow season, but flood events during the high flow season resulted in high degrees of change in the flows, e.g.…”
Section: Hydrocynus Vittatusmentioning
confidence: 94%
“…These extreme changes in flows are brought about by increased anthropogenic water use placing pressure on the quantity of available water to meet environmental water reserve criteria (Saraiva Okello et al 2015). These anthropogenic stressors increase fish stress as flow and temperature move into intolerable conditions (Rivers-Moore et al 2013;Ramulifho et al 2019). Fish telemetered studies can detect changes of behaviour in response to these extreme flows and temperature fluctuations and, if not mitigated, can negatively affect the populations of fishes in the rivers studied (Burnett et al 2020;2021a).…”
Section: Hydrocynus Vittatusmentioning
confidence: 99%
“…To increase the efficiency and compatibility of hydrological methods with the ecosystem of each region, an echohydrological method (combination of ecological and hydrological methods) is used. Selecting the adequate ecosystem conservation criteria [20][21][22] in allocating e-flows 23,24 is one of the most important challenges in estimating the appropriate e-flow for a basin in ecohydrological methods 25 . To determine the class of hydrological environmental management and e-flow allocation 26,27 hydraulic methods 28 have been used in some studies.…”
mentioning
confidence: 99%